2014
DOI: 10.4314/evj.v17i1.9
|View full text |Cite
|
Sign up to set email alerts
|

A bilobed Gallbladder (Vesica Fellea Divisa) in Cattle Slaughtered at Jimma Municipal Abattoir, West Oromiya, Ethiopia

Abstract: Gallbladder abnormalities occur rarely. The recognized abnormalities recorded so far comprised duplication, septation, abnormal position and total absence of the gallbladder. The bilobed gallbladder of the cross bred oxen slaughtered at Jimma municipality abattoir constituted two lobes separated by a deep cleft. However, the two lobes were joined at the neck and drained by one duct. Both the lobes were of equal size and filled with bile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was found that 11 of the 12 isolates tested were resistant in cattle to recommended doses of isometamidium and homidium. Since then, several other reports have emerged substantiating the widespread occurrence of trypanocidal drug resistance in many parts of the country [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 11 of the 12 isolates tested were resistant in cattle to recommended doses of isometamidium and homidium. Since then, several other reports have emerged substantiating the widespread occurrence of trypanocidal drug resistance in many parts of the country [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%